THE FUTURE OF FOG COMPUTING IN KENYA - Ndungi, Rebeccah; Sugiantoro, Bambang (American Journal of Computing and Engineering, 2021)
The study, titled "The Future of Fog Computing in Kenya," discusses fog computing, computing evolution, and the Internet of Things. It has layers ideal for fog networks. The architecture depicts the functions performed by each layer, the protocols, devices, and their functionality at various layers. Fog computing extends cloud computing and helps mitigate its difficulties. The study also goes forth to explain the various sectors where fog-computing technology is applied and the various merits associated with it. In order to improve present technology, this article will greatly help researchers in Kenya and beyond by giving ideas and suggestions as a way to focus on the COUNTRY'S VISION 2030.